PEMBELAJARAN KOLABORATIF SEBAGAI STRATEGI INOVATIF DALAM MENINGKATKAN KETERLIBATAN PESERTA DIDIK DI ERA DIGITAL - Elsa Oktavia; Kana (JURNAL PENDIDIKAN DAN KEGURUAN, 2025)
The collaborative learning model is a learning approach that emphasizes cooperation between students in achieving shared learning goals. Technological developments and the demands of 21st-century learning require an active, participatory, and student-oriented learning process. This article aims to examine the basic concepts of the collaborative learning model, identify the benefits of its application, and describe effective strategies for implementing collaborative learning. The method used is a literature study by analyzing various sources in the form of books and relevant scientific articles. The results of the study indicate that the collaborative learning model can improve learning interactions, social skills, reflective thinking skills, and student learning outcomes. In addition, collaborative learning encourages students to be more active, responsible, and able to work together in groups. However, its implementation requires careful planning, effective group management, and the role of the teacher as a learning facilitator. With the right strategy, the collaborative learning model can be an effective and relevant learning alternative to improve the quality of the learning process at various levels of education